What is Documediality and why Traces, Documents and Archives are Normative - Maurizio Ferraris; Valeria Martino (Law Text Culture, 2018)
The documedia revolution is a technological, social, and anthropological revolution. It has indeed been possible thanks to the constructive force of documentality in conjunction with the communicative and mobilizing power of the web. It is a connection between documents and media that has involved a very large number of people, in a completely unexpected way. Therefore, it can be defined anthropological because it directly concerns human beings, modifies their lifestyle in more than one way and at the same time highlights some essential human characteristics; it can be considered social because it is given in the social world at the base of which there is documentality; it is technological because it is triggered by the strength and peculiarity of the web.